2021
DOI: 10.1186/s12915-021-01110-4
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies variation of larval locomotion kinematics in the genus Drosophila and its relation to habitat temperature

Abstract: Background Speed and trajectory of locomotion are the characteristic traits of individual species. Locomotion kinematics may have been shaped during evolution towards increased survival in the habitats of each species. Although kinematics of locomotion is thought to be influenced by habitats, the quantitative relation between the kinematics and environmental factors has not been fully revealed. Here, we performed comparative analyses of larval locomotion in 11 Drosophila species. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…To understand the extent of species-specific characteristics maintenance in laboratory strains and the presence of intraspecific variation in certain Drosophila species, we need to comparatively analyze many different strains, including freshly-established different local strains and other laboratory-maintained strains. Previously, the laboratory strains of 11 Drosophila species have been used for comparative studies of the embryonic development and the larval locomotor behavior 33 , 34 . Interestingly, the correlation between species-specific characteristics and their natural habitats has been reported with the laboratory strains 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the extent of species-specific characteristics maintenance in laboratory strains and the presence of intraspecific variation in certain Drosophila species, we need to comparatively analyze many different strains, including freshly-established different local strains and other laboratory-maintained strains. Previously, the laboratory strains of 11 Drosophila species have been used for comparative studies of the embryonic development and the larval locomotor behavior 33 , 34 . Interestingly, the correlation between species-specific characteristics and their natural habitats has been reported with the laboratory strains 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the laboratory strains of 11 Drosophila species have been used for comparative studies of the embryonic development and the larval locomotor behavior 33 , 34 . Interestingly, the correlation between species-specific characteristics and their natural habitats has been reported with the laboratory strains 34 . Therefore, the experimental results using laboratory strains, including our study, should be valuable benchmarks for future comparative analyses in understanding the exact species-specific characteristics and adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that this observation could allow us to predict neural circuits for fly larval crawling. A recent study reported an inter-specific variation in crawling speed among eleven species in the genus Drosophila [ 57 ]. This study showed that some sister species crawled faster than Drosophila melanogaster , and the others locomoted slower.…”
Section: Resultsmentioning
confidence: 99%
“…12 ). To compensate the difference in experimental conditions between this study and Matsuo et al [ 57 ], the speed of each species was normalized by the speed of Drosophila melanogaster . To analyse the dependency on w En , the dependency of w ES was averaged out from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation